Role of intraoperative squash smear cytology as a diagnostic modality in lipoma of quadrigeminal cistern - Majumdar, Kaushik (Medknow Publications & Media Pvt Ltd, 2013)
Quadrigeminal lipoma is a rare tumor that has been categorized as developmental malformation rather than a hamartoma or true neoplasm, due to its origin from abnormal persistence and mal-differentiation of meninx primitiva during the development of the subarachnoid cisterns. Reported admixture of adipose tissue with heterotopic elements also supports a developmental origin. Quadrigeminal lipomas are frequently asymptomatic and detected incidentally. Though a favorable clinical course is usually expected, recurrences may occur due to partial removal of lesions in close relation to vital structure. We describe the role of intraoperative squash smear cytology as a diagnostic aid in quadrigeminal cistern lipoma and an alternative to frozen sections that are technically difficult to obtain due to presence of lobules of fibro-adipose tissue. With radiological correlation, squash cytology can be an economical method for intraoperative diagnosis, pending subsequent histopathological confirmation.